2018
DOI: 10.1038/s41598-018-22055-9
|View full text |Cite|
|
Sign up to set email alerts
|

Femtosecond Laser Mass Spectrometry and High Harmonic Spectroscopy of Xylene Isomers

Abstract: Structural isomers, molecules having the same chemical formula but with atoms bonded in different order, are hard to identify using conventional spectroscopy and mass spectrometry. They exhibit virtually indistinguishable mass spectra when ionized by electrons. Laser mass spectrometry based on photoionization of the isomers has emerged as a promising alternative but requires shaped ultrafast laser pulses. Here we use transform limited femtosecond pulses to distinguish the isomers using two methods. First, we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Although the HOMO has the highest probability of tunnel ionization, it has been experimentally and theoretically observed that the laser polarization direction that favors tunnel ionization from the inner valence such as HOMO−1 or HOMO−2 could be achievable. Thus, the difference in the ionization probability from the HOMO becomes smaller, and ionization from the inner valence also weakly contributes as a subchannel. Angle-dependent ionization probabilities based on the shape of the HOMO have also been reported for organic compounds containing aromatic rings , or halogens and for electronically excited molecules …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the HOMO has the highest probability of tunnel ionization, it has been experimentally and theoretically observed that the laser polarization direction that favors tunnel ionization from the inner valence such as HOMO−1 or HOMO−2 could be achievable. Thus, the difference in the ionization probability from the HOMO becomes smaller, and ionization from the inner valence also weakly contributes as a subchannel. Angle-dependent ionization probabilities based on the shape of the HOMO have also been reported for organic compounds containing aromatic rings , or halogens and for electronically excited molecules …”
Section: Introductionmentioning
confidence: 98%
“…Thus, the difference in the ionization probability from the HOMO becomes smaller, and ionization from the inner valence also weakly contributes as a subchannel. 16−21 Angle-dependent ionization probabilities based on the shape of the HOMO have also been reported for organic compounds containing aromatic rings 22,23 or halogens 24 and for electronically excited molecules. 25 In this study, the femtosecond-laser ionization mass spectra of linear saturated hydrocarbons, n-pentane (C 5 H 12 ) and nhexane (C 6 H 14 ), were measured using the femtosecond-laser ionization mass spectrometry of fragment ions under a laser field intensity of 0.18−3.9 × 10 14 W cm −2 with 800 nm central wavelength and 100 fs pulse width.…”
Section: Introductionmentioning
confidence: 99%
“…After separation, recognition often requires the use of expensive instrumental methods, including gas‐phase mass spectrometry and nuclear magnetic resonance (NMR) spectroscopy, and complicated operations (e.g., multistep sample treatment; Figure 1 a ). [ 12 ] Moreover, because of their extensive applications and high volatility, these organic isomers are often found in the atmosphere, particularly in production workshops, which not only leads to significant environmental problems, such as photochemical smog and ozonosphere holes, but also causes direct and indirect harm to the human body. [ 13 ] In this context, we envisioned that the development of new functional materials that simultaneously recognize and separate organic isomers would be highly desirable for fundamental research and industrial production.…”
Section: Introductionmentioning
confidence: 99%